The Q.Theatre database: Don Quixote on the European scene - Fernández Ferreiro, María; Álvarez Álvarez, María (Talía. Revista de estudios teatrales, 2021)
The multiple tools that new technologies offer to Humanistic studies help researchers in their work, and promote and assist in the transfer of their results. In this respect, databases have proven to be one of the most useful and practical tools for both researchers and the general audience. This article presents and describes the Q.Theatre database, one of the results of the homonymous European project, coordinated by the University of Oviedo. It brings together plays that adapt or version Miguel de Cervantes’ Don Quixote, created all over Europe from the first appearance of the novel to the present day.